Looking Beyond Initial Boost: Examining the Long - Term Performance of Small Business IPOs - Siwach, Parveen; Kumar, R. Prasanth; Gupta, Vikas (Indian Journal of Finance, 2024)
Purpose : The study aimed to analyze the long-run performance of 383 Indian SME IPOs offered from 2012 to 2020. Methodology : The article used event time methods to examine company performance by creating equal and value-weighted portfolios. Furthermore, the study employed calendar time portfolios with the Fama-French three-factor model and Carhart four-factor model to have robust results. The study used cross-sectional regression to examine factors shaping IPO performance. Findings : Using 12-month buy-and-hold abnormal returns, the results demonstrated IPO overperformance for both equally weighted and value-weighted portfolios, while the positive alpha of calendar-time portfolios validated these findings for the same period. However, regression outcomes revealed IPO underperformance for 36-month calendar-time portfolios. The findings indicated a significant impact of issue size, oversubscription, debt-to-asset ratio, profitability, hot market conditions, and listing gains. Practical Implications : Practical implications suggested informed IPO decisions, cautious IPO assessment, and risk management for IPO investors and other stakeholders. Originality : The study employed different approaches and investigated various significant aspects, providing valuable insights for investors and market players.